Tính:
\(\dfrac{5}{8}+\dfrac{3}{5}\times\dfrac{5}{12}\) = ...
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: \(\dfrac{3}{9}\times\dfrac{5}{4}=\dfrac{5}{4}\times\dfrac{1}{3}=\dfrac{5\times1}{4\times3}=\dfrac{5}{12}\)
b: \(\dfrac{10}{15}\times\dfrac{3}{5}=\dfrac{3}{5}\times\dfrac{2}{3}=\dfrac{3\times2}{5\times3}=\dfrac{2}{5}\)
c: \(\dfrac{5}{8}\times\dfrac{4}{12}=\dfrac{5}{8}\times\dfrac{1}{3}=\dfrac{5}{3\times8}=\dfrac{5}{24}\)
d: \(\dfrac{9}{27}\times\dfrac{3}{21}=\dfrac{1}{7}\times\dfrac{1}{3}=\dfrac{1\times1}{7\times3}=\dfrac{1}{21}\)
a)
\(\dfrac{3}{5}\times\dfrac{7}{11}\times\dfrac{5}{3}\times11\\ =\left(\dfrac{3}{5}\times\dfrac{5}{3}\right)\times\left(\dfrac{7}{11}\times11\right)\\ =\dfrac{3\times5}{5\times3}\times\dfrac{7\times11}{11}\\ =1\times7\\ =7\)
b)
\(\dfrac{3}{8}\times\dfrac{2}{7}+\dfrac{5}{7}\times\dfrac{3}{8}\\ =\dfrac{3}{8}\times\left(\dfrac{2}{7}+\dfrac{5}{7}\right)\\ =\dfrac{3}{8}\times\dfrac{7}{7}\\ =\dfrac{3}{8}\times1=\dfrac{3}{8}\)
a) \(\dfrac{2}{4}\times\dfrac{9}{5}=\dfrac{1}{2}\times\dfrac{9}{5}=\dfrac{1\times9}{2\times5}=\dfrac{9}{10}\)
b) \(\dfrac{13}{8}\times\dfrac{5}{15}=\dfrac{13}{8}\times\dfrac{1}{3}=\dfrac{13}{24}\)
c) \(\dfrac{3}{9}\times\dfrac{6}{12}=\dfrac{1}{3}\times\dfrac{1}{2}=\dfrac{1}{3\times2}=\dfrac{1}{6}\)
a: =18/20=9/10
b: \(=\dfrac{13\cdot5}{8\cdot15}=\dfrac{13}{8}\cdot\dfrac{1}{3}=\dfrac{13}{24}\)
c: \(=\dfrac{1}{3}\cdot\dfrac{1}{2}=\dfrac{1}{6}\)
a,\(4+\dfrac{5}{9}=\dfrac{4}{1}+\dfrac{5}{9}=\dfrac{36}{9}+\dfrac{5}{9}=\dfrac{41}{9}\)
b,\(\dfrac{8}{3}-2=\dfrac{8}{3}-\dfrac{2}{1}=\dfrac{8}{3}-\dfrac{6}{3}=\dfrac{2}{3}\)
c,\(\dfrac{5}{12}x\dfrac{4}{15}=\dfrac{20}{180}=\dfrac{2}{18}=\dfrac{1}{6}\)
d,\(5:\dfrac{15}{8}=\dfrac{5x8}{15}=\dfrac{40}{15}=\dfrac{8}{3}\)
a)\(\dfrac{4}{1}+\dfrac{5}{9}=\dfrac{36}{9}+\dfrac{5}{9}=\dfrac{41}{9}\)
b) \(\dfrac{8}{3}-\dfrac{2}{1}=\dfrac{8}{3}-\dfrac{6}{3}=\dfrac{2}{3}\)
\(\dfrac{5}{12}x\dfrac{4}{15}=\dfrac{20}{180}=\dfrac{1}{9}\)
\(\dfrac{5x8}{15}=\dfrac{40}{15}=\dfrac{8}{3}\)
\(\dfrac{5}{3}\times\dfrac{15}{8}-\dfrac{9}{8}\times\dfrac{5}{8}-\dfrac{5}{3}\)
\(=\dfrac{5}{3}\times\left(\dfrac{15}{8}-\dfrac{9}{8}-1\right)\)
\(=\dfrac{5}{3}\times\left(\dfrac{15}{8}-\dfrac{9}{8}-\dfrac{8}{8}\right)\)
\(=\dfrac{5}{3}\times\dfrac{-1}{4}\)
\(=-\dfrac{5}{12}\)
a) $\frac{2}{5} \times \frac{3}{8} \times \frac{3}{4} = \frac{{2 \times 3 \times 3}}{{5 \times 8 \times 4}} = \frac{{18}}{{160}} = \frac{9}{{80}}$
b) $\frac{1}{3} \times \frac{1}{6} \times \frac{1}{9} = \frac{{1 \times 1 \times 1}}{{3 \times 6 \times 9}} = \frac{1}{{162}}$
c) $\frac{3}{4}:\frac{1}{5}:\frac{7}{8} = \frac{3}{4} \times \frac{5}{1} \times \frac{8}{7} = \frac{{3 \times 5 \times 8}}{{4 \times 1 \times 7}} = \frac{{120}}{{28}} = \frac{{30}}{7}$
d) $\frac{3}{5}:\frac{1}{5}:\frac{3}{8} = \frac{3}{5} \times \frac{5}{1} \times \frac{8}{3} = \frac{{3 \times 5 \times 8}}{{5 \times 1 \times 3}} = 8$
a, \(4\times\left(-\dfrac{1}{2}\right)^3-2\times\left(-\dfrac{1}{2}\right)^2+3\times\left(-\dfrac{1}{2}\right)+1\)
\(=\left(-\dfrac{1}{2}\right)\left[\left(4\times-\dfrac{1}{2}\right)-\left(2\times-\dfrac{1}{2}\right)+3\right]+1\)
\(=\left(-\dfrac{1}{2}\right)\left(-2+1+3\right)+1\)
\(=\left(-\dfrac{1}{2}\right)2+1\)
\(=-1+1\)
\(=0\)
@Trịnh Thị Thảo Nhi
a, 4×(−12)3−2×(−12)2+3×(−12)+14×(−12)3−2×(−12)2+3×(−12)+1
=(−12)[(4×−12)−(2×−12)+3]+1=(−12)[(4×−12)−(2×−12)+3]+1
=(−12)(−2+1+3)+1=(−12)(−2+1+3)+1
=(−12)2+1=(−12)2+1
=−1+1=−1+1
=0=0
\(\dfrac{5}{8}+\dfrac{3}{5}\times\dfrac{5}{12}=\dfrac{5}{8}+\dfrac{3\times5}{5\times12}=\dfrac{5}{8}+\dfrac{3}{12}=\dfrac{5}{8}+\dfrac{1}{4}=\dfrac{5+2\times1}{8}=\dfrac{7}{8}\)
\(\dfrac{5}{8}+\dfrac{3}{5}\)x \(\dfrac{5}{12}\)
= \(\dfrac{5}{8}+\dfrac{1}{4}=\dfrac{5+2}{8}=\dfrac{7}{8}\)